ULAMA'S POLITICAL STRUGGLING IN STRENGTHENING WASATHIYAH ISLAM IN THE PALACE - Pagar, Pagar; Akhyar, Syaiful (State Islamic University of North Sumatra Indonesia, 2025)
The magnitude of the ulema's obsession to color power in Indonesia is reflected in the fierceness of their battle in the 2019 presidential election. The direct involvement of the ulama made this political event special and different from the previous presidential elections throughout Indonesian history. What's special about this event is that it started from the views of scholars;